Ploidy and domestication are associated with genome size variation in Palms1. Issue 10 (5th October 2015) - Gunn, Bee F.; Baudouin, Luc; Beulé, Thierry; Ilbert, Pascal; Duperray, Christophe; Crisp, Michael; Issali, Auguste; Konan, Jean‐Louis; Rival, Alain
Abstract : PREMISE OF THE STUDY: The genome size of a species (C‐value) is associated with growth, development and adaptation to environmental changes. Angiosperm C‐values range 1200‐fold and frequently vary within species, although little is known about the impacts of domestication on genome size. Genome size variation among related species of palms is of evolutionary significance because changes characterize clades and may be associated with polyploidy, transposon amplifications, deletions, or rearrangements. Further knowledge of genome size will provide crucial information needed for planning of whole genome sequencing and accurate annotations. We studied the genome size of Cocos nucifera and its variation among cultivars, and compared it to values for related palms from the Attaleinae subtribe. METHODS: Flow cytometric analysis of isolated nuclei from young palm leaves was used to estimate genome sizes of 23 coconut cultivars (Talls, Dwarfs, and hybrids) worldwide and 17 Cocoseae species. Ancestral genome size was reconstructed on a maximum likelihood phylogeny of Attaleinae from seven WRKY loci. KEY RESULTS: The coconut genome is large—averaging 5.966 pg—and shows intraspecific variation associated with domestication. Variation among Tall coconuts was significantly greater than among Dwarfs. Attaleinae genomes showed moderate size variation across genera, except polyploids Jubaeopsis caffra, Voanioala gerardii, Beccariophoenix alfredii, and Allagoptera caudescens, which had larger genomes. CONCLUSIONS: Our results contribute to the understanding of the relationship between domestication and genome size in long‐lived tree crops and provide a basis for whole‐genome sequencing of the coconut and other domesticated plants. Polyploidy evolved independently in two clades within Attaleinae.